Clinical indicators of sexual dysfunction in pregnant women: integrative literature review. - Carteiro, Dora Maria Honorato; Ribeiro de Sousa, Lisete Maria; Alves Caldeira, Sílvia Maria (Revista Brasileira de Enfermagem)
Objective: to identify the nursing diagnosis clinical indicators of sexual dysfunction in pregnant women. Method: it is an integrative literature review, with research in databases using the keywords "sexual*", "pregnan*" and "function*". Studies included had an abstract available for analysis, referring to pregnant women over 18 years old, written in Portuguese, French, Spanish and English, with publication date between 2010 and 2014. Studies that reporting pregnant women with an associated pathology were excluded. Results: sexual dysfunction in pregnant women is consistent in the literature. Nine defining characteristics were identified and 16 related factors, some not classified in NANDA International. Conclusion: clinical indicators can be added to the nursing diagnosis to favor an accurate diagnosis and effective interventions in the surveillance of pregnancy as a period of healthy sexual experience.